THE ROLE OF AIR POLLUTION IN THE DEVELOPMENT OF CARDIOVASCULAR DISEASES - Tadjieva Kh. S; Kosimova Kh. T.; Niyazova O. A. (The Conference Hub, 2025)
The environmental issues of the 21st century have a serious impact on human health. Air pollution is one of the most pressing problems, reducing the quality of life for millions of people worldwide and contributing to the development of various chronic diseases, particularly cardiovascular diseases.